Development of Polymeric and Polymer-Based Hybrid Adsorbents for Chromium Removal from Aqueous Solution - Kaya, Ismet Gul Buyruklardan; Duranoglu, Dilek; Beker, Ulker; Senkal, Bahire Filiz (WILEY, 2011)
Ferric oxide-loaded hybrid sorbents are environmentally benign and exhibit sorption behaviors for chromium removal from waters. In the current study, glycidyl methacrylate-based polymer (GMD) and nanosized ferric oxide loaded glycidyl methacrylate-based polymer (GMDFe) were prepared and assayed to examine the effect of ferric oxide loading on chromium sorption from aqueous solution for the first time from the equilibrium and kinetic points of view. The experimental equilibrium data, suitably fitted by the Langmuir and Freundlich isotherms, have shown that ferric oxide loaded hybrid sorbent exhibits higher adsorption capacity than glycidyl methacrylate-based polymer (GMD). The Langmuir isotherm model was found to be the most suitable one for the Cr(VI) adsorption. The maximum adsorption capacities of GMD and GMDFe sorbents were determined at pH 4 as 109.54 and 157.52 mg/g, respectively. A series of column experiments was carried out to determine the breakthrough curves. The column was regenerated by eluting Cr(VI) using NaOH (10% w/v) solution after adsorption studies.
Keywords: Chromium; Ferric oxide; Nanoparticle; Pollution; Wastewater; WASTE-WATER; METAL-IONS; CR(VI); ADSORPTION; NANOPARTICLES; BIOSORPTION; KINETICS; WASTEWATERS; PARAMETERS; SEPARATION; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources